A case of gestational gigantomastia in a 37-years-old woman associated with elevated ANA: a casual linkage? - Zingaretti, Nicola (Pan Afr Med J, 2017)
Hypertrophy of the breast (macromastia and gigantomastia) is a rare medical condition of the breast connective tissues. The etiology of this condition is still not clear; rarely, gigantomastia has been reported to develop in the setting of an autoimmune illness. We reported a case of a 37-years-old woman with undifferentiated connective tissue disease of 2-years duration presented with enlargement of breasts. The breast enlargment started at 5 months of gestation. She successfully underwent reduction mammoplasty with free nipple graft. In the succeeding months the level of antinuclear ANA remained stable. It is uncertain whether a positive antinuclear antibodies in gigantomastia is a casuative agent or an effect.